Functional A Posteriori Error Estimates for Time-Periodic Parabolic Optimal Control Problems. (2nd October 2016) - Langer, Ulrich; Repin, Sergey; Wolfmayr, Monika
ABSTRACT: This article is devoted to the a posteriori error analysis of multiharmonic finite element approximations to distributed optimal control problems with time-periodic state equations of parabolic type. We derive a posteriori estimates of the functional type, which are easily computable and provide guaranteed upper bounds for the state and co-state errors as well as for the cost functional. These theoretical results are confirmed by several numerical tests that show high efficiency of the a posteriori error bounds.